Magnet material, permanent magnet, rotating electric machine, and vehicle
A magnet material with controlled composition and crystal structure enhances coercive force and magnetization, addressing the need for smaller and more efficient rotating electric machines and vehicles.
Patent Information
- Application Number
- JP2023038542
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-03-14
- Filing Date
- 2023-03-13
- Publication Date
- 2024-12-23
- Estimated Expiration
- 2040-03-12
AI Technical Summary
The challenge is to enhance the coercive force of permanent magnets used in various applications, particularly in rotating electric machines and vehicles, to meet the demand for smaller and more efficient products.
A magnet material composition with specific ratios of rare earth elements, Fe and Co, Nb, and B, forming a crystalline phase with controlled crystal grain sizes and grain boundary phases, achieving high coercive force and residual magnetization.
The solution results in magnets with coercive force of 500 kA/m or more and residual magnetization of 0.84 T or more, suitable for smaller and more efficient motors and generators.
Smart Images

Figure 0007604539000003 
Figure 0007604539000004 
Figure 0007604539000005
Abstract
Description
[Technical field]
[0001] The embodiments relate to a magnet material, a permanent magnet, a rotating electric machine, and a vehicle. [Background technology]
[0002] Permanent magnets are used in a wide range of products including, for example, rotating electrical machines such as motors and generators, electrical equipment such as speakers and measuring instruments, and vehicles such as automobiles, railway cars, etc. In recent years, there has been a demand for miniaturization and high efficiency in the above-mentioned products, and there is a demand for high-performance permanent magnets with high magnetization and high coercive force.
[0003] Examples of high-performance permanent magnets include rare earth magnets such as Sm-Co magnets and Nd-Fe-B magnets. In these magnets, Fe and Co contribute to increasing the saturation magnetization. These magnets also contain rare earth elements such as Nd and Sm, which provide large magnetic anisotropy due to the behavior of the 4f electrons of the rare earth elements in the crystal field. This allows for a large coercive force to be obtained. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent No. 4320701 [Patent Document 2] JP 2004-263232 A [Patent Document 3] Japanese Patent Application Publication No. 9-74006 Summary of the Invention [Problem to be solved by the invention]
[0005] The problem to be solved by the present invention is to increase the coercivity of a magnetic material. [Means for solving the problem]
[0006] The magnetic material of the embodiment is represented by the composition formula 2: (R 1-uY u ) x Nb y B t M 100-x-y-t (R is at least one element selected from the group consisting of rare earth elements, M is at least one element selected from the group consisting of Fe and Co, x is a number satisfying 4≦x≦11 atomic %, and y is 1.0 ≦y≦6.5 atomic %, t is a number satisfying 0≦t<12 atomic %, and u is a number satisfying 0.01≦u≦0.5), 12 The compound semiconductor material has at least one structure selected from the group consisting of a TbCu7 type crystal structure and a TbCu7 type crystal structure, and z defined by z=(100-xyt) / (x+y) is a number satisfying 7.5≦z≦12. The intrinsic coercive force is 500 kA / m or more and the residual magnetization is 0.84 T or more. [Brief description of the drawings]
[0007] [Figure 1] FIG. 1 illustrates an example of a permanent magnet motor. [Diagram 2] FIG. 1 illustrates an example of a variable magnetic flux motor. [Diagram 3] FIG. 1 illustrates an example of a generator. [Figure 4] FIG. 1 is a schematic diagram showing an example of the configuration of a railway vehicle. [Diagram 5] FIG. 1 is a schematic diagram showing an example of the configuration of an automobile. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] Hereinafter, the embodiments will be described with reference to the drawings. Note that the drawings are schematic, and for example, the relationship between thickness and planar dimensions, the ratio of thicknesses of each layer, etc. may differ from the actual ones. In addition, in the embodiments, substantially the same components are given the same reference numerals, and the description will be omitted.
[0009] (First embodiment) The magnet material of the embodiment contains a rare earth element, an M element (M is at least one element selected from the group consisting of Fe and Co), an Nb element, and an B element. The magnet material has a metal structure in which a crystalline phase containing a high concentration of the M element is the main phase. The saturation magnetization can be improved by increasing the concentration of the M element in the main phase. The main phase is the phase that has the highest volume occupancy among the crystalline phases and amorphous phases in the magnet material. The magnet material may contain a subphase. The subphase is, for example, a grain boundary phase, a fine crystalline phase, an impurity phase, or the like that exists between the crystal grains of the main phase. An example of a crystalline phase containing a high concentration of the M element is ThMn. 12 The TbCu7 type crystal phase can be used as a crystal phase.
[0010] In addition to rare earth elements and M, the addition of Nb and B elements can improve the ability to form an amorphous structure and increase the coercive force. One of the applications of the above magnetic materials is bonded magnets and motors that use them. In recent years, there has been an increasing demand for smaller and faster motors, and this has led to an increased demand for improved heat resistance of magnets. In order to improve heat resistance, it is necessary to improve the coercive force.
[0011] In a magnetic material having a large magnetic anisotropy, one of the effective methods for expressing coercivity is to refine the crystal grains in the magnetic material. Therefore, it is preferable that the main phase has microcrystals. The microcrystals are formed, for example, by producing an amorphous ribbon using a liquid quenching method and then subjecting it to an appropriate heat treatment to cause the precipitation and growth of crystal grains.
[0012] By miniaturizing the main phase with high magnetic anisotropy, each crystal grain is more likely to be in a single magnetic domain state, suppressing the generation of reverse magnetic domains and the propagation of magnetic domain walls, and exhibiting high coercivity. If the crystal grain size is too fine or too large, the coercivity decreases, so the average crystal grain size of the main phase is preferably 0.1 nm to 100 nm, more preferably 0.5 nm to 80 nm, even more preferably 1 nm to 60 nm, and even more preferably 3 nm to 50 nm. In addition, the squareness ratio can be improved by narrowing the grain size distribution of the main phase.
[0013] A non-magnetic or weakly magnetic grain boundary phase may be formed as the grain boundary phase. Thereby, the magnetic coupling between the crystal grains is cut off, the effect of suppressing the generation of reverse magnetic domains and the propagation of magnetic walls is enhanced, and the coercive force can be improved.
[0014] In order to increase the coercive force, it is necessary to control the addition amounts of the rare earth element, M element, Nb element, and B element. The magnet material of the embodiment has, for example, the composition formula 1: R x Nb y B t M 100-x-y-t represented by. Note that the magnet material may contain inevitable impurities.
[0015] The R element is a rare earth element, which brings a large magnetic anisotropy to the magnet material and can impart a high coercive force to the permanent magnet. Specifically, the R element is at least one element selected from the group consisting of yttrium (Y), lanthanum (La), cerium (Ce), praseodymium (Pr), neodymium (Nd), promethium (Pr), samarium (Sm), europium (Eu), gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), thulium (Tm), ytterbium (Yb), and lutetium (Lu). In particular, it is preferable to use Sm. For example, when using a plurality of elements containing Sm as the R element, by setting the Sm concentration to 50 atomic% or more of all the elements applicable as the R element, the performance of the magnet material, such as the coercive force, can be enhanced.
[0016] The addition amount x of the R element is preferably a number that satisfies, for example, 6.2 < x ≦ 8 atomic%. If x is too small or too large, a heterogeneous phase will precipitate and the coercive force will decrease. The addition amount x of the R element is more preferably a number that satisfies 6.3 ≦ x ≦ 7.7 atomic%, further preferably a number that satisfies 6.4 ≦ x ≦ 7.5 atomic%, and still further preferably a number that satisfies 6.5 ≦ x ≦ 7.4 atomic%.
[0017] Niobium (Nb) is an element that is effective in stabilizing the crystalline phase containing a high concentration of the M element. It is also an element that is effective in promoting amorphization. The performance of the magnetic material, for example, the coercive force, can be improved by adjusting the amount of Nb added, y, to satisfy a specific relational expression with the amount of R added, x. The amount of Nb added, y, is preferably a number that satisfies, for example, 0.75≦x / (x+y)≦0.95.
[0018] When x / (x+y) is less than 0.75, the Sm concentration in the crystal structure decreases, the magnetic anisotropy of the magnet material decreases, and the stability of the main phase decreases. For example, the α-Fe phase and the R2Fe phase 14 It becomes difficult to obtain a high coercive force due to reasons such as the tendency for the alloy to decompose into the B phase.
[0019] If x / (x+y) is greater than 0.95, the amount of Nb becomes too small, making it difficult to form an amorphous material, and the coercive force decreases. A number that satisfies 0.76≦x / (x+y)≦0.93 is more preferable, and a number that satisfies 0.77≦x / (x+y)≦0.9 is even more preferable.
[0020] 50 atomic % or less of Nb element may be replaced with at least one element selected from the group consisting of zirconium (Zr), tantalum (Ta), and hafnium (Hf). Zr element, Ta element, and Hf element are elements effective for stabilizing the crystal phase and making it amorphous.
[0021] The M element is at least one element selected from the group consisting of Fe and Co, and is an element that is responsible for the high saturation magnetization of the magnetic material. Since Fe has a higher magnetization than Co, it is preferable that 50 atomic % or more of the M element is Fe. By adding Co to the M element, the Curie temperature of the magnetic material increases, and the decrease in saturation magnetization in the high temperature region can be suppressed. In addition, by adding a small amount of Co, the saturation magnetization can be increased more than when Fe is used alone. On the other hand, increasing the Co ratio leads to a decrease in the anisotropic magnetic field. Furthermore, if the Co ratio is too high, the saturation magnetization also decreases. For this reason, by appropriately controlling the ratio of Fe to Co, it is possible to simultaneously achieve high saturation magnetization, high anisotropic magnetic field, and high Curie temperature. When M in composition formula 1 is (Fe 1-y Co y ), the preferred value of y is 0.01≦y<0.7, more preferably 0.01≦y<0.5, and even more preferably 0.01≦y≦0.3. 20 atomic % or less of the M element may be replaced with at least one element selected from the group consisting of aluminum (Al), silicon (Si), chromium (Cr), manganese (Mn), nickel (Ni), vanadium (V), titanium (Ti), copper (Cu), tantalum (Ta), tungsten (W), molybdenum (Mo), and gallium (Ga). The above elements contribute to the growth of crystal grains that constitute the main phase, for example.
[0022] Boron (B) is an element effective in promoting amorphization. By appropriately controlling the amount t of B element added, it is possible to obtain an amorphous ribbon by a method with high industrial productivity such as the single roll quenching method. The amount t of B element added is preferably a number that satisfies, for example, 0≦t<12 atomic %. When the amount of B element is too much, it becomes R2Fe 14 A heterophase such as a B phase is easily formed, and the coercive force is reduced. Although amorphization is possible even if the B element is not substantially contained, when using a single roll method, it is necessary to increase the roll peripheral speed to increase the cooling rate, which reduces industrial productivity. The amount t of the B element added is more preferably a number that satisfies 0.5≦t≦11 atomic %, even more preferably a number that satisfies 1≦t≦10.8 atomic %, and even more preferably a number that satisfies 2≦t≦10.5 atomic %.
[0023] A part of the R element may be replaced by the Y element. In this case, the magnetic material may be, for example, a material having the composition formula 2: (R 1-u Y u ) x Nb y B t M 100-x-y-t The magnet material may contain inevitable impurities. The above explanations of the R element, Nb element, B element, and M element may be appropriately used.
[0024] The Y element is a crystalline phase containing a high concentration of the M element, e.g., ThMn 12 It is an element effective for stabilizing the TbCu7 type crystal phase and the TbCu7 type crystal phase. The higher the M element concentration is, the higher the saturation magnetization of the crystal phase containing a high concentration of the M element is, and the higher the magnetic properties can be improved. However, as the M element concentration increases, the crystal structure becomes unstable, and the coercive force decreases due to the decomposition of the main phase and the precipitation of the α-Fe or α-(Fe,Co) phase. In contrast, by substituting a part of the R element with the Y element, the stability of the crystal phase containing a high concentration of the M element can be improved, and the M element concentration can be further increased. This makes it possible to achieve both high coercive force and high magnetization. The amount of Y element added, u, is preferably a number that satisfies 0.01≦u≦0.5 atomic %. If u is too small, the stabilizing effect is small, and if u is too large, the magnetic anisotropy decreases and the coercive force decreases. It is more preferable that u is a number that satisfies 0.02≦u≦0.4 atomic %, and even more preferably 0.05≦u≦0.3 atomic %.
[0025] In the magnet material represented by Composition Formula 1 or Composition Formula 2, the value of z defined by (100 - x - y - t) / (x + y) is proportional to the addition amount of element M, and the higher the value of z, the higher the magnetization obtained. It is preferable that z is a number satisfying 7.5 ≤ z ≤ 12. When z is less than 7.5, the concentration of element M becomes low and the magnetization decreases. When z is greater than 12, precipitation of α-Fe or α-(Fe, Co) phase cannot be avoided and the coercive force decreases. More preferably, z is a number satisfying 8 ≤ z ≤ 12, still more preferably 8.5 ≤ z ≤ 12, still more preferably a number satisfying 9 < z ≤ 12, and still more preferably a number satisfying 9.5 ≤ z ≤ 12. In the case of the magnet material represented by Composition Formula 2, preferably it is a number satisfying 9 < z ≤ 12, and still more preferably a number satisfying 9.5 ≤ z ≤ 12. By substituting a part of R with Y, the stability of the crystal phase containing a high concentration of element M is improved, and it becomes easier to increase the coercive force in a composition with a large value of z.
[0026] In the magnet material represented by Composition Formula 2, the addition amounts x of element R and Y and the addition amount y of Nb are preferably numbers respectively satisfying 4 ≤ x ≤ 11 atomic% and 0 ≤ y ≤ 6.5 atomic%, but more preferably y is a number satisfying 0.75 ≤ x / (x + y) ≤ 0.95. Still more preferably, it is a number satisfying 0.76 ≤ x / (x + y) ≤ 0.93, and still more preferably a number satisfying 0.77 ≤ x / (x + y) ≤ 0.9. Also, more preferably, x is a number satisfying 6.2 < x ≤ 8 atomic%, still more preferably a number satisfying 6.3 ≤ x ≤ 7.7 atomic%, still more preferably a number satisfying 6.4 ≤ x ≤ 7.5 atomic%, and still more preferably a number satisfying 6.5 ≤ x ≤ 7.4 atomic%.
[0027] The magnet material of the embodiment may further include an element A. The element A is at least one element selected from the group consisting of nitrogen (N), carbon (C), hydrogen (H), and phosphorus (P). The element A penetrates into the crystal lattice and has the function of causing at least one of expanding the crystal lattice and changing the electronic structure. This makes it possible to change the Curie temperature, magnetic anisotropy, and saturation magnetization. The element A does not necessarily have to be added, except as an unavoidable impurity.
[0028] The magnet material of the embodiment may be in the form of a quenched alloy ribbon produced by a liquid quenching method (melt spun method), or may be, for example, in the form of powder using the quenched alloy ribbon as a raw material. The ribbon preferably has an average thickness of 10 μm to 60 μm. If the ribbon is too thin, the proportion of a surface deteriorated layer increases, and the magnetic properties, for example, magnetization, decrease. If the ribbon is too thick, a distribution of the cooling rate is likely to occur within the ribbon, and the coercive force decreases. The average thickness of the ribbon is preferably 15 μm to 50 μm, and more preferably 20 μm to 40 μm.
[0029] The intrinsic coercivity of the magnet material of the embodiment is 300 kA / m or more and 2500 kA / m or less. In order to improve heat resistance, it is more preferably 500 kA / m or more and 2500 kA / m or less, even more preferably 600 kA / m or more and 2500 kA / m or less, even more preferably 610 kA / m or more and 2500 kA / m or less, even more preferably 620 kA / m or more and 2500 kA / m or less, and even more preferably 640 kA / m or more and 2500 kA / m or less.
[0030] The residual magnetization of the magnetic material of the embodiment is 0.7 T or more and 1.6 T or less. The higher the residual magnetization, the more effective it is for reducing the size of the motor. The residual magnetization is preferably 0.75 T or more and 1.6 T or less, and more preferably higher than 0.8 T and 1.6 T or less.
[0031] The composition of the magnet material is measured by, for example, Inductively Coupled Plasma-Atomic Emission Spectroscopy (ICP-AES), Scanning Electron Microscope-Energy Dispersive X-ray Spectroscopy (SEM-EDX), Transmission Electron Microscope-Energy Dispersive X-ray Spectroscopy (TEM-EDX), Scanning Transmission Electron Microscope-Energy Dispersive X-ray Spectroscopy (STEM-EDX), etc. The volume ratio of each phase is determined comprehensively by combining observation with an electron microscope or optical microscope with X-ray diffraction, etc.
[0032] The average grain size of the main phase is determined as follows. Among the main phase crystal grains identified using STEM-EDX in the cross section of the magnetic material, an arbitrary grain is selected, and the longest straight line A is drawn for the selected grain, with both ends touching another phase. Next, at the midpoint of line A, a line B is drawn that is perpendicular to line A and touches both ends of another phase. The average of the lengths of lines A and B is defined as the diameter D of the phase. Using the above procedure, D is determined for one or more arbitrary phases. The above D is calculated for five fields of view for one sample, and the average of all D is defined as the diameter (D) of the phase. The cross section of the magnetic material is taken from substantially the center of the surface having the largest area of the sample.
[0033] The average thickness of the quenched alloy ribbon can be determined, for example, as follows: A ribbon piece having a thickness of 10 mm or more is measured for thickness using a micrometer. The average thickness of the ribbon is calculated by measuring the thickness of 10 or more ribbon pieces and averaging the values excluding the maximum and minimum values.
[0034] The magnetic properties of the magnetic material, such as the coercive force and magnetization, are calculated using, for example, a vibrating sample magnetometer (VSM).
[0035] Next, an example of a method for manufacturing the magnetic material of the embodiment will be described. First, an alloy containing the predetermined elements required for the magnetic material is manufactured. For example, the alloy can be manufactured using an arc melting method, a high-frequency melting method, a mold casting method, a mechanical alloying method, a mechanical grinding method, a gas atomizing method, a reduction diffusion method, or the like.
[0036] The alloy is melted and quenched. This makes the alloy amorphous. The molten alloy is cooled, for example, by a liquid quenching method (melt spun method). In the liquid quenching method, the molten alloy is injected into a roll rotating at high speed. The roll may be a single roll type or a twin roll type, and is mainly made of copper or the like. The cooling rate of the molten alloy can be controlled by controlling the amount of molten alloy injected and the peripheral speed of the rotating roll. The degree of amorphization of the alloy can be controlled by the composition and the cooling rate. In addition, if an amorphous alloy has already been obtained by using a gas atomization method or the like during the preparation of the alloy, it is not necessary to carry out a quenching process again.
[0037] The amorphous alloy or alloy ribbon is subjected to a heat treatment. This allows the main phase to be crystallized, forming a metal structure having a main phase with microcrystals. For example, the alloy or alloy ribbon is heated at a temperature of 500°C to 1000°C for 5 minutes to 300 hours in an inert atmosphere such as Ar or vacuum.
[0038] If the temperature is too low, the crystallization and homogenization are insufficient, and the coercive force decreases. If the temperature is too high, a different phase is generated due to decomposition of the main phase, and the coercive force and squareness decrease. The heating temperature is, for example, more preferably 520°C to 800°C, even more preferably 540°C to 700°C, and even more preferably 550°C to 650°C. If the heating time is too short, the crystallization and homogenization are insufficient, and the coercive force decreases.
[0039] If the heating time is too long, a different phase is generated due to decomposition of the main phase, and the coercive force and squareness are reduced. The heating time is preferably 15 minutes or more and 150 hours or less, more preferably 30 minutes or more and 120 hours or less, more preferably 1 hour or more and 120 hours or less, more preferably 2 hours or more and 100 hours or less, and more preferably 3 hours or more and 80 hours or less.
[0040] After heating, the crystallized alloy or ribbon is cooled by a method such as furnace cooling, water quenching, gas quenching, or oil quenching.
[0041] The A element may be infiltrated into the alloy. It is preferable to pulverize the alloy into powder before the step of infiltrating the A element into the alloy. When the A element is nitrogen, the alloy is nitrided by heating the alloy at a temperature of 200°C to 700°C for 1 hour to 100 hours in an atmosphere of nitrogen gas or ammonia gas at a pressure of about 0.1 to 100 atmospheres, and the N element can be infiltrated into the alloy. When the A element is carbon, the alloy is carbonized by heating the alloy at a temperature range of 300°C to 900°C for 1 hour to 100 hours in an atmosphere of C2H2, CH4, C3H8, or CO gas or methanol pyrolysis gas at a pressure of about 0.1 to 100 atmospheres, and the C element can be infiltrated into the alloy. When the A element is hydrogen, the alloy is hydrogenated by heating the alloy at a temperature range of 200 to 700°C for 1 to 100 hours in an atmosphere of hydrogen gas or ammonia gas at a pressure of about 0.1 to 100 atmospheres, and the H element can be infiltrated into the alloy. When the A element is phosphorus, the alloy can be phosphorized and the P element can be introduced into the alloy.
[0042] A magnetic material is produced by the above process. The alloy or ribbon is pulverized to produce magnetic powder. A permanent magnet is produced by using the magnetic material or magnetic powder. An example of a magnet production process is shown below.
[0043] By pressure-sintering a magnet material, a permanent magnet having a sintered body can be formed. As methods of pressure-sintering, methods such as heating and sintering after pressing with a press molding machine, methods using a spark plasma sintering method, methods using a hot press, and methods using a hot working method can be applied. For example, the magnet material is pulverized using a pulverizing device such as a jet mill or a ball mill, and a molded body is obtained by magnetic field orientation pressing at a pressure of about 1 ton in a magnetic field of about 1 to 2 T. The obtained molded body is heated and sintered in an inert gas atmosphere such as Ar or in a vacuum to produce a sintered body. A permanent magnet can be manufactured by appropriately applying heat treatment to the sintered body in an inert atmosphere or the like.
[0044] Also, a bonded magnet can be manufactured by pulverizing the above magnet material and fixing and mixing the pulverized material with a binder. As the binder, for example, a thermosetting resin, a thermoplastic resin, a low melting point alloy, a rubber material, etc. can be used. As the molding method, for example, a compression molding method or an injection molding method can be used.
[0045] The magnetic properties of the bonded magnet, particularly the residual magnetization and the maximum magnetic energy product, can be enhanced by increasing the density of the bonded magnet. Also, by reducing the voids of the bonded magnet due to densification, the corrosion resistance can be improved.
[0046] The densified bonded magnet may have, for example, a magnet material represented by the composition formula 3:R x Nb y B t M 100-x-y-t R is at least one element selected from the group consisting of rare earth elements, M is at least one element selected from the group consisting of Fe and Co, x is a number satisfying 4.0 < x ≦ 11.0 atomic%, y is a number satisfying 0 ≦ y ≦ 6.5, and t is a number satisfying 0 ≦ t < 12 atomic%. Other descriptions of the magnet material can be appropriately referred to the description of the above magnet material.
[0047] It is difficult to achieve high density with ribbon-shaped magnetic materials due to factors such as friction that occurs between the materials during molding and spring back of the material itself.
[0048] In order to increase the density of the bonded magnet, the compression molding process is carried out at a rate of 6 x 10 2 It is effective to alternate between a pressurizing step, in which a pressurizing pressure of 100 MPa or more is applied, followed by a depressurizing step, in which the pressurizing pressure is reduced to 90% or less of the pressurizing pressure in the pressurizing step. By switching between pressurizing and depressurizing, the binder and material flow progresses in a direction that homogenizes the internal stress, while releasing localized residual stress due to springback and causing plastic deformation of the material, thereby reducing the voids in the bonded magnet and achieving high density. The density of the bonded magnet is, for example, 6.45 g / cm 3 More than 7.8g / cm 3 The density of the bonded magnet is more preferably 6.53 g / cm or less. 3 It is.
[0049] The pressure in the pressurization step is 6.0×10 2 MPa or more 3.0×10 3 MPa or less is preferable. 6.0×10 2 If the pressure is less than 3.0×10 MPa, the force to make the material and binder flow is insufficient, so the effect of reducing voids is low. 3 If the pressure exceeds 8.0×10 MPa, the pressure is too strong, requiring special molds and equipment, and reducing productivity. 2 MPa or more 2.5×10 3 MPa or less, and more preferably 10.0×10 2 MPa or more 2.0×10 3 MPa or less.
[0050] In the depressurization step, it is preferable to release the pressure to atmospheric pressure, but industrially, by leaving a pressure equal to or higher than atmospheric pressure, the lead time can be shortened and productivity can be improved. The pressure in the depressurization step is preferably 90% or less of the pressure in the pressurization step. If the pressure exceeds 90% of the pressure in the pressurization step, the residual stress is not sufficiently released in the depressurization step, and the flow of the material and binder is difficult to proceed. The pressure in the depressurization step is more preferably 60% or less of the pressure in the pressurization step, and even more preferably 30% or less of the pressure in the pressurization step. The lower limit of the pressure in the depressurization step is atmospheric pressure, and if the pressure is less than atmospheric pressure, i.e., in a reduced pressure state, a separate pressure reducing device is required, which significantly reduces productivity.
[0051] It is preferable to repeat the switching between the pressurizing step and the depressurizing step two or more times. If it is repeated once, there is little flow after the residual stress is released, and the effect of reducing voids is low. The number of switching times is more preferably three or more, even more preferably five or more, and even more preferably ten or more. The upper limit of the number of switching times is preferably, for example, 20 or less. If it is repeated more than 20 times, there are too few remaining voids, so the material and binder do not flow, and the effect of densification is low.
[0052] The average length of the magnetic material used for the bonded magnet is preferably 5 μm or more and 1 mm or less. If it is less than 5 μm, the flow of the material and binder due to pressurization and depressurization does not easily occur, making it difficult to improve the density. If it exceeds 1 mm, the surface roughness of the bonded magnet increases, reducing the dimensional accuracy. The lower limit of the average length is, for example, more preferably 20 μm or more, even more preferably 50 μm or more, even more preferably 100 μm or more, even more preferably 150 μm or more, even more preferably 200 μm or more. The upper limit of the average length is, for example, more preferably 800 μm or less, even more preferably 500 μm or less. By appropriately controlling the average length, the effect of improving density by repeating the pressurization step and the depressurization step can be increased, and the density can be increased to, for example, 6.53 g / cm. 3 It is possible to realize a bonded magnet having a density as high as or higher.
[0053] The density of a bonded magnet is determined from the dimensions and weight of the molded body. To further improve the dimensional accuracy, the bonded magnet may be subjected to a grinding process or the like before measurement. The average length of the magnetic material can be controlled, for example, by sieving. The average length may also be controlled by adjusting the grinding conditions, such as the grinding time and screen diameter, of various grinding devices, such as a cutter mill or a hammer mill. The average length can be defined, for example, by determining the length in the long side direction of 50 or more powder particles from an SEM image and averaging the values.
[0054] During compression molding, a press pressure may be applied by applying a rotational or reciprocating motion to a molding die such as a pestle or a die, which applies a force such as a shear force, thereby achieving high density.
[0055] The binder of the bonded magnet includes resins such as epoxy resin, nylon resin, polyamide resin, polyimide resin, silicone resin, etc. The resin may be powdered resin, liquid resin, or a mixture of these resin forms, but liquid resin is particularly useful for increasing the density of the bonded magnet. The viscosity of the liquid resin is preferably 1 poise or more and 500 poise or less.
[0056] The binder content is preferably 0.5% by mass or more and 5% by mass or less. If it exceeds 5% by mass, the magnetic properties are significantly reduced. If it is less than 0.5% by mass, the binding force is insufficient and sufficient strength cannot be obtained. The binder content is preferably 1% by mass or more and 4% by mass or less, and more preferably 2% by mass or more and 3% by mass or less.
[0057] The bonded magnet may contain a coupling material such as a titanium-based coupling material or a silicon-based coupling material. The coupling agent has the effect of improving the dispersibility of the powder, and is effective in increasing the magnet density. The density of the magnet material can be increased by surface-treating it with a lubricant such as fatty acid, fatty acid salts, amines, or amine acids.
[0058] Second embodiment A permanent magnet having the magnetic material of the first embodiment can be used in various motors and generators. It can also be used as a fixed magnet or a variable magnet of a variable magnetic flux motor or a variable magnetic flux generator. Various motors and generators are configured by using the permanent magnet of the first embodiment. When the permanent magnet of the first embodiment is applied to a variable magnetic flux motor, the technology disclosed in, for example, JP 2008-29148 A or JP 2008-43172 A can be applied to the configuration and drive system of the variable magnetic flux motor.
[0059] Next, a motor and a generator equipped with the above-mentioned permanent magnet will be described with reference to the drawings. FIG. 1 is a diagram showing a permanent magnet motor. In the permanent magnet motor 11 shown in FIG. 1, a rotor 13 is arranged in a stator 12. A permanent magnet 15, which is the permanent magnet of the first embodiment, is arranged in an iron core 14 of the rotor 13. By using the permanent magnet of the first embodiment, it is possible to achieve high efficiency, miniaturization, and cost reduction of the permanent magnet motor 11 based on the characteristics of each permanent magnet. In addition, the permanent magnet can be inserted into the flux barrier portion of a synchronous reluctance motor. This can increase the power factor of the synchronous reluctance motor.
[0060] FIG. 2 is a diagram showing a variable magnetic flux motor. In the variable magnetic flux motor 21 shown in FIG. 2, a rotor 23 is disposed in a stator 22. The permanent magnets of the first embodiment are disposed in an iron core 24 of the rotor 23 as a fixed magnet 25 and a variable magnet 26. The magnetic flux density (amount of magnetic flux) of the variable magnet 26 can be varied. Since the magnetization direction of the variable magnet 26 is perpendicular to the Q-axis direction, it is not affected by the Q-axis current and can be magnetized by the D-axis current. A magnetization winding (not shown) is provided on the rotor 23. By passing a current from a magnetization circuit through this magnetization winding, the magnetic field directly acts on the variable magnet 26.
[0061] According to the permanent magnet of the first embodiment, it is possible to obtain a coercive force suitable for the fixed magnet 25. When the permanent magnet of the first embodiment is applied to the variable magnet 26, the manufacturing conditions may be changed to control the coercive force, for example, to a range of 100 kA / m to 500 kA / m. In the variable magnetic flux motor 21 shown in FIG. 2, the permanent magnet of the first embodiment may be used for both the fixed magnet 25 and the variable magnet 26, but the permanent magnet of the first embodiment may be used for either one of the magnets. The variable magnetic flux motor 21 is capable of outputting a large torque with a small device size, and is therefore suitable for motors for hybrid vehicles, electric vehicles, and the like, which require high output and compactness of the motor.
[0062] Fig. 3 shows a generator. The generator 31 shown in Fig. 3 includes a stator 32 using the above-mentioned permanent magnet. A rotor 33 arranged inside the stator 32 is connected to a turbine 34 provided at one end of the generator 31 via a shaft 35. The turbine 34 rotates, for example, by a fluid supplied from the outside. Note that instead of the turbine 34 rotated by a fluid, it is also possible to rotate the shaft 35 by transmitting dynamic rotation such as regenerative energy of an automobile. Various known configurations can be adopted for the stator 32 and the rotor 33.
[0063] The shaft 35 is in contact with a commutator (not shown) arranged on the opposite side of the rotor 33 to the turbine 34, and electromotive force generated by the rotation of the rotor 33 is boosted to a system voltage as the output of the generator 31 via a phase separation bus and a main transformer (not shown) and transmitted. The generator 31 may be either a normal generator or a variable magnetic flux generator. The rotor 33 is charged by static electricity from the turbine 34 and by an axial current accompanying power generation. For this reason, the generator 31 is provided with brushes 36 for discharging the charge on the rotor 33.
[0064] As described above, by applying the above-mentioned permanent magnet to a generator, it is possible to obtain effects such as high efficiency, miniaturization, and low cost.
[0065] The rotating electric machine may be mounted, for example, on a railway vehicle (one example of a vehicle) used for railway transportation. FIG. 4 is a diagram showing one example of a railway vehicle 100 equipped with a rotating electric machine 101. The motors shown in FIGS. 1 and 2, the generator shown in FIG. 3, or the like can be used as the rotating electric machine 101. When the rotating electric machine is mounted as the rotating electric machine 101, the rotating electric machine 101 may be used as an electric motor (motor) that outputs driving force by utilizing, for example, power supplied from an overhead line or power supplied from a secondary battery mounted on the railway vehicle 100, or may be used as a generator (generator) that converts kinetic energy into electric power and supplies the power to various loads in the railway vehicle 100. By using a highly efficient rotating electric machine such as the rotating electric machine of the embodiment, the railway vehicle can be run with reduced energy.
[0066] The rotating electric machine may be mounted on an automobile (another example of a vehicle) such as a hybrid automobile or an electric automobile. FIG. 5 is a diagram showing an example of an automobile 200 equipped with a rotating electric machine 201. The motors shown in FIGS. 1 and 2, the generator shown in FIG. 3, or the like can be used as the rotating electric machine 201. When the rotating electric machine is mounted as the rotating electric machine 201, the rotating electric machine 201 may be used as an electric motor that outputs the driving force of the automobile 200, or as a generator that converts the kinetic energy of the automobile 200 during its travel into electric power. The rotating electric machine may also be mounted on, for example, industrial equipment (industrial motors), air conditioning equipment (air conditioner / water heater compressor motors), wind power generators, or elevators (hoists). EXAMPLES
[0067] (Examples 1 to 4) The raw materials were weighed in appropriate amounts, and an alloy was produced using the arc melting method. Next, the alloy was melted, and the resulting molten metal was quenched using the single roll method to produce a quenched alloy ribbon. The alloy ribbon was heated at 650°C for 4 hours in an Ar atmosphere, and gas quenched. The composition of the magnetic material was evaluated using ICP-AES. In addition, the coercivity of the permanent magnet was evaluated using VSM. The evaluation results of the composition, coercivity, and remanence of the magnetic material are shown in Table 1.
[0068] (Examples 5-9) The raw materials were weighed in appropriate amounts, and an alloy was produced using the arc melting method. Next, the alloy was melted, and the resulting molten metal was quenched using the single roll method to produce a quenched alloy ribbon. The alloy ribbon was heated at 630°C for 12 hours in an Ar atmosphere, and gas quenched. The composition of the magnetic material was evaluated using ICP-AES. In addition, the coercivity and remanence of the permanent magnet were evaluated using VSM. The evaluation results of the composition, coercivity, and remanence of the magnetic material are shown in Table 1.
[0069] (Examples 10-16) The raw materials were weighed in appropriate amounts, and an alloy was produced using the arc melting method. Next, the alloy was melted, and the resulting molten metal was quenched using the single roll method to produce a quenched alloy ribbon. The alloy ribbon was heated at 600°C for 30 hours in an Ar atmosphere, and gas quenched. The composition of the magnetic material was evaluated using ICP-AES. In addition, the coercivity and remanence of the permanent magnet were evaluated using VSM. The evaluation results of the composition, coercivity, and remanence of the magnetic material are shown in Table 1.
[0070] (Comparative Example 1-3) The raw materials were weighed in appropriate amounts, and an alloy was produced using the arc melting method. Next, the alloy was melted, and the resulting molten metal was quenched using the single roll method to produce a quenched alloy ribbon. The alloy ribbon was heated at 640°C for 1 hour in an Ar atmosphere, and gas quenched. The composition of the magnetic material was evaluated using ICP-AES. In addition, the coercivity and remanence of the permanent magnet were evaluated using VSM. The evaluation results of the composition, coercivity, and remanence of the magnetic material are shown in Table 1. The evaluation results of the composition, coercivity, and remanence of the magnetic material are shown in Table 1.
[0071] [Table 1]
[0072] As shown in Table 1, the magnet materials of Examples 1-16 are represented by composition formula 1 or composition formula 2, and z, defined by z=(100-xyt) / (x+y), is a number that satisfies 7.5≦z≦12. The magnet materials of Examples 1-16 are TnMn 12The main phase has at least one crystal phase selected from the group consisting of a TbCu7 type crystal phase and a TbCu7 type crystal phase. Furthermore, the magnet materials of Examples 1-16 have an intrinsic coercivity of 610 kA / m or more and a residual magnetization of more than 0.80 T.
[0073] (Examples 17-19) After preparing a magnetic material in the same manner as in Examples 10-16, the magnetic material was pulverized so that the average length was 200 μm or more and 500 μm or less. The pulverized powder, epoxy resin, and titanium coupling agent were weighed out to be 97.0 mass%, 2.5 mass%, and 0.5 mass%, respectively, and an appropriate amount of acetone was added and mixed. The acetone was then volatilized to prepare a mixed powder. The obtained mixed powder was filled into a mold, and then 10.0×10 2 A pressurizing step in which a pressure of 100 MPa is applied to pressurize the filler, followed by a depressurizing step in which the pressure is reduced to atmospheric pressure, was alternately repeated five times to produce a molded body. The resulting molded body was heat-treated at 130°C for one hour to produce a bonded magnet, whose density and magnetic properties were evaluated. Table 2 shows the composition of the magnetic material, and the evaluation results of the density, residual magnetization, and maximum magnetic energy product of the bonded magnet. The residual magnetization and maximum magnetic energy product were measured using a BH tracer.
[0074] (Examples 20 and 21) A magnetic material was prepared in the same manner as in Examples 10-16, and the magnetic material was pulverized so that the average length was 100 μm or more and 200 μm or less. The pulverized powder, epoxy resin, and titanium coupling agent were weighed out to be 97.0 mass%, 2.5 mass%, and 0.5 mass%, respectively, and an appropriate amount of acetone was added and mixed. The acetone was then volatilized to prepare a mixed powder. The obtained mixed powder was filled into a mold, and then 10.0 × 10 2A pressurizing step in which a pressure of 100 MPa is applied to pressurize the filler, followed by a depressurizing step in which the pressure is reduced to atmospheric pressure, was alternately repeated five times to produce a molded body. The resulting molded body was heat-treated at 130°C for one hour to produce a bonded magnet, whose density and magnetic properties were evaluated. Table 2 shows the composition of the magnetic material, and the evaluation results of the density, residual magnetization, and maximum magnetic energy product of the bonded magnet. The residual magnetization and maximum magnetic energy product were measured using a BH tracer.
[0075] Comparative Example 4 A magnetic material was prepared in the same manner as in Examples 10-16, and the magnetic material was pulverized so that the average length was 200 μm or more and 500 μm or less. The pulverized powder, epoxy resin, and titanium coupling agent were weighed out to be 97.0 mass%, 2.5 mass%, and 0.5 mass%, respectively, and an appropriate amount of acetone was added and mixed. The acetone was then volatilized to prepare a mixed powder. The obtained mixed powder was filled into a mold, and then 10.0 × 10 2 A compact was produced by performing a pressurizing step in which a pressure of 100 MPa was applied to pressurize the filler, followed by a depressurizing step in which the pressure was reduced to atmospheric pressure once each. The resulting compact was heat-treated at 130°C for one hour to produce a bonded magnet, whose density and magnetic properties were evaluated. Table 2 shows the composition of the magnetic material, and the evaluation results of the density, residual magnetization, and maximum magnetic energy product of the bonded magnet. The residual magnetization and maximum magnetic energy product were measured using a BH tracer.
[0076] Comparative Example 5 A magnetic material was prepared in the same manner as in Examples 10-16, and the magnetic material was pulverized so that the average length was 100 μm or more and 200 μm or less. The pulverized powder, epoxy resin, and titanium coupling agent were weighed out to be 97.0 mass%, 2.5 mass%, and 0.5 mass%, respectively, and an appropriate amount of acetone was added and mixed. The acetone was then volatilized to prepare a mixed powder. The obtained mixed powder was filled into a mold, and then 10.0 × 10 2A compact was produced by performing a pressurizing step in which a pressure of 100 MPa was applied to pressurize the filler, followed by a depressurizing step in which the pressure was reduced to atmospheric pressure once each. The resulting compact was heat-treated at 130°C for one hour to produce a bonded magnet, whose density and magnetic properties were evaluated. Table 2 shows the composition of the magnetic material, and the evaluation results of the density, residual magnetization, and maximum magnetic energy product of the bonded magnet. The residual magnetization and maximum magnetic energy product were measured using a BH tracer.
[0077] [Table 2]
[0078] As shown in Table 2, the bonded magnets of Examples 17-21 had a density of 6.45 g / cm 3 This shows that the density of the bonded magnet can be improved by adjusting the manufacturing conditions of the bonded magnet.
[0079] It should be noted that the above embodiments are presented as examples and are not intended to limit the scope of the invention. These novel embodiments can be implemented in various other forms, and various omissions, substitutions, and modifications can be made without departing from the spirit of the invention. These embodiments and their modifications are included in the scope and spirit of the invention, and are included in the scope of the invention and its equivalents described in the claims. [Explanation of symbols]
[0080] 11...permanent magnet motor, 13...rotor, 14...iron core, 15...permanent magnet, 21...variable magnetic flux motor, 23...rotor, 24...iron core, 25...fixed magnet, 26...variable magnet, 31...generator, 32...stator, 33...rotor, 34...turbine, 35...shaft, 36...brush, 100...railroad vehicle, 101...rotating electric motor, 200...automobile, 201...rotating electric motor.
Claims
1. Composition formula 2: (R 1-u Y u ) x Nb y B t M 100-x-y-t (R is at least one element selected from the group consisting of rare earth elements, M is at least one element selected from the group consisting of Fe and Co, x is a number satisfying 4≦x≦11 atomic %, y is a number satisfying 1.0≦y≦6.5 atomic %, t is a number satisfying 0≦t<12 atomic %, and u is a number satisfying 0.01≦u≦0.5) is represented by TnMn 12 Type crystal structure and TbCu 7 The present invention has at least one structure selected from the group consisting of a type crystal structure, z is defined as z=(100-x-y-t) / (x+y), and is a number satisfying 7.5≦z≦12; A magnetic material having an intrinsic coercive force of 500 kA / m or more and a residual magnetization of 0.84 T or more.
2. The magnetic material according to claim 1 , wherein z is a number satisfying 9<z≦12.
3. 3. The magnetic material according to claim 1, having an intrinsic coercivity of 600 kA / m or more.
4. 4. The magnetic material according to claim 1, having a residual magnetization of 0.91 T or more.
5. The magnetic material according to claim 1 , having a main phase having the at least one structure.
6. The magnetic material according to claim 5, wherein the main phase has an average crystal grain size of 0.1 nm or more and 100 nm or less.
7. 7. The magnetic material according to claim 1, wherein 50 atomic % or more of the R element is Sm.
8. 8. The magnetic material according to claim 1, wherein 50 atomic % or less of Nb element is substituted with at least one element selected from the group consisting of Zr, Hf, and Ta.
9. 9. The magnetic material according to claim 1, wherein 50 atomic % or more of the M element is Fe.
10. 10. The magnetic material according to claim 1, wherein 20 atomic % or less of the M element is substituted with at least one element selected from the group consisting of Ni, Cu, V, Cr, Mn, Al, Si, Ga, Ta, W, Ti, and Mo.
11. y is a number satisfying 1.5≦y≦6.5 atomic %. The magnetic material according to any one of claims 1 to 10.
12. A magnetic material according to any one of claims 1 to 11, A binder; A permanent magnet comprising:
13. The density of the permanent magnet is 6.45 g / cm 3 The permanent magnet according to claim 12 .
14. The density of the permanent magnet is 6.53 g / cm 3 The permanent magnet according to claim 12 .
15. A permanent magnet comprising a sintered body of the magnetic material according to any one of claims 1 to 11.
16. A stator; A rotor; A rotating electric machine, wherein the stator or the rotor comprises the permanent magnet according to any one of claims 12 to 15.
17. The rotating electric machine according to claim 16 , wherein the rotor is connected to a turbine via a shaft.
18. A vehicle comprising the rotating electric machine according to claim 16.
19. 20. The vehicle of claim 18, wherein the rotor is connected to a shaft to transmit rotation to the shaft.
Citation Information
Patent Citations
Permanent magnet
JP1995066021A
Magnetic material and bonded magnet
JP1997074006A
Permanent magnet material and bonded magnet
JP1999003812A
Permanent magnet and manufacture thereof
JP2000114016A
Permanent magnet and material thereof
JP2000114017A
